GEOLOGY AND CHARACTERISTICS OF LOW SULPHIDATION EPITHERMAL VEIN IN SENEPO AREA, EAST JAVA - Arifudin Idrus; Esti Handayani (Puslitbang tekMIRA, 2017)
Senepo area is one of several epithermal mineralization prospects in Southern Mountains of Java Island. This study is aimed to investigate the geological framework and hydrothermal alteration of the prospect as well as to characterize the low sulphidation (LS) epithermal vein including vein textures, ore mineral, ore chemistry and hydrothermal fluid that are responsible for the formation of the quartz vein. Detailed field mapping was completed to understand the geological framework and hydrothermal alteration zones. Petrographic, ore microscopic, XRD and AAS analyses were applied to characterize the quartz vein. The study area is occupied by pebbly sandstone, andesite breccia, andesite units and alluvial deposit. Ore mineralization is mainly hosted by andesite of Oligo-Miocene of Watupatok Formation. The host-rock has been suffered by overprinted hydrothermal alteration and weathering. The epithermal veins are found as N-S-trending quartz veins with a thickness of 1-2 meters. These veins show massive texture, crustiform, cockade, druzy, comb, and disseminated sulphides, which is included in Crystalline Quartz Zonation (X). Optical microscopy and XRD analysis indicate that these veins contain several ore minerals such as chalcopyrite, sphalerite, galena, pyrite, hematite, covellite and malachite, associated with gangue mineral including quartz, felspar, chlorite and clay minerals. AAS analysis displays variable chemical composition of precious and base metals such as Au (17-37 ppb), Ag (8.1-32.6 ppm), Cu (122.1-81,450 ppm), Pb (35.4-883.6 ppm) and Zn (18.3-2,628 ppm). Gold and silver are relatively low compared to the base metals. Fluid inclusion micro thermometric analysis indicates that ore mineralization originated at temperatures of 187-263 oC and salinity of 0.18-0.53 % wt. NaCl eq. This salinity corresponds with a minimum hydrostatic pressure of about 10-55.1 bars. Based on those characteristic data, mineralized quartz veins in the study area are classified into a base metal horizon of LS epithermal system.